Influence of pesticides on male fertility - Bretveld, Reini; Brouwers, Marijn; Ebisch, Inge; Roeleveld, Nel (Scandinavian Journal of Work, Environment & Health, 2007)
Several studies have shown a decline in human semen quality and increased risks of male subfertility. This paper provides an overview of the mechanisms of pesticide-induced reproductive toxicity and the effects on male fertility since exposure to pesticides may be one of the causes of these disorders. Pesticides may directly damage spermatozoa, alter Sertoli cell or Leydig cell function, or disrupt the endocrine function in any stage of hormonal regulation (hormone synthesis, release, storage, transport, and clearance; receptor recognition and binding; thyroid function; and the central nervous system). These mechanisms are described with respect to the effects of pesticide exposure in vitro and in vivo. In epidemiologic studies, effects on sperm quality and time to pregnancy are reviewed. Clear effects on male fertility have been demonstrated for some pesticides [eg, dibromochloropropane, ethylene dibromide]. But results from more recent studies are inconsistent, and no uniform conclusion can be drawn about the effects of pesticides on male reproduction.
Keywords: endocrine disrupting chemical; hormone regulation; male fertility; overview; pesticide; review; sperm quality; time to pregnancy